Relationship between extractable chlorophyll content and SPAD values in three varieties of Kacip Fatimah under greenhouse conditions - Ibrahim, Mohd Hafiz; Jaafar, Hawa Z. E. (Taylor & Francis Group, 2013)
Relationship between extractable chlorophyll and relative chlorophyll values obtained using Soil Plant Analytical Development (SPAD)-502 meter were determined in three varieties of Labisia pumila (alata, pumila, lanceolata) under greenhouse conditions using fresh weight basis. The experiment was arranged as a complete randomized design replicated three times with each experimental unit containing five plants. There were no significant differences (P ≥ 0.05) for all the three varieties in their chlorophyll a, b and total. Best fit relationship was found to be linear in chlorophyll a, b and total (P ≤ 0.01) with ascending slope as SPAD values intensified. Chlorophyll b was higher than chlorophyll a in all the varieties indicating species as shade-loving plants. The chlorophyll content of L. pumila leaves can be conveniently determined using SPAD-502 chlorophyll meter, a technique providing simple, rapid, and nondestructive method to estimate leaf chlorophyll content which could also be an indicator of leaf nitrogen (N) status.